On the Sensitivity of Stability Results to the Choice of the Numeraire - Mukherji, Anjan (Review of Economic Studies, 1973)
Journal Article On the Sensitivity of Stability Results to the Choice of the Numeraire Get access Anjan Mukherji Anjan Mukherji University of Rochester and Jawaharlal Nehru University, New Delhi Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 40, Issue 3, July 1973, Pages 427–433, https://doi.org/10.2307/2296462 Published: 01 July 1973